2001
DOI: 10.1016/s0377-1237(01)80007-1
|View full text |Cite
|
Sign up to set email alerts
|

Serological Diagnosis of Toxoplasma Gondii Infection in Various Patient Population in the Armed Forces

Abstract: The study included 200 healthy age and sex matched controls (120 healthy volunteers and 80 healthy antenatal cases without any bad obstetric history) and 300 cases comprising patients with bad obstetric history (BOH) 80 cases, seizure or encephalitis 50 cases, cervical lymphadenopathy 30 cases, congenital deformity 30 cases, HIV infected 80 cases and patients on long term immunosuppression 30 cases. Anti-toxoplasma IgG & Igl\l were measured by ELISA and lndivlduals found positive for anti Toxoplasma gondii IgM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…3 There are, however, reports of marked increases in toxoplasma IgG titers greater than 4-fold above normal limits in cases of acute toxoplasmosis infection. 7 Although it is unclear why our patient's toxoplasma IgM and polymerase chain reaction studies were negative, her ophthalmic examination, multimodal imaging findings, history of travel and high-risk exposure, and positive response to antiparasitic therapy ultimately supported our clinical diagnosis of ocular toxoplasmosis.…”
Section: Discussionmentioning
confidence: 59%
“…3 There are, however, reports of marked increases in toxoplasma IgG titers greater than 4-fold above normal limits in cases of acute toxoplasmosis infection. 7 Although it is unclear why our patient's toxoplasma IgM and polymerase chain reaction studies were negative, her ophthalmic examination, multimodal imaging findings, history of travel and high-risk exposure, and positive response to antiparasitic therapy ultimately supported our clinical diagnosis of ocular toxoplasmosis.…”
Section: Discussionmentioning
confidence: 59%
“…More specific confirmatory tests was used, like a dye test or immunoblotting (Lesle et al, 2011). Praharaj et al (2001) in India reported bad obstetric outcome (patients with history of repeated abortions, still births and giving birth to babies with congenital abnormalities) was one of the commonest presentations of Toxoplasma infection during pregnancy. Nogareda et al (2014) in France reported that repeated monthly testing continues during pregnancy in high-risk was a must.…”
Section: Introductionmentioning
confidence: 99%